Religiusitas dan Karakteristik Pekerjaan pada Tingkat Komitmen Organisasi di Toserba Syariah: Studi pada Karyawan Muslim - Latifah, Umi; Wibowo, Ugung DA; Setyawati, Rr; Mildaeni, Itsna Nurrahma (Universitas Muhammadiyah Purwokerto, 2022)
This study investigates the influence of religiosity and job characteristics on organizational commitment among Muslim employees in the operational department of a Sharia department store in Banjar City. Employing a quantitative research approach, the study encompasses a population sample of 61 Muslim employees. Data was collected using validated instruments, including the religiosity scale (Cronbach's α = 0.863), job characteristics scale (Cronbach's α = 0.923), and organizational commitment scale (Cronbach's α = 0.914). Multiple regression analysis was conducted to assess the relationships between the variables. The results indicate a significant impact of both religiosity and job characteristics on organizational commitment, with a significance value of p = 0.000 (p < 0.05). Specifically, religiosity and job characteristics account for 52.9% of the variance in organizational commitment, suggesting that these factors are critical to enhancing employee engagement. Other variables not included in this study contribute to the remaining 47.1% of the variance. Based on these findings, it is recommended that management in Sharia department stores foster an environment that supports religious practices and aligns job characteristics with employees' values and expectations. This could involve integrating religious observances into workplace policies and tailoring job roles to enhance alignment with employee values. Future research should explore additional factors influencing organizational commitment, such as leadership styles and workplace culture, to provide a more comprehensive understanding of the dynamics at play.